Efficacy of Immediate Switching from Bicalutamide to Flutamide as Second-Line Combined Androgen Blockade. (14th July 2016) - Yokomizo, Yumiko; Kawahara, Takashi; Miyoshi, Yasuhide; Otani, Masako; Yamanaka, Shoji; Teranishi, Jun-ichi; Noguchi, Kazumi; Yao, Masahiro; Uemura, Hiroji
Abstract : We determined whether prostate specific antigen (PSA) would decrease with immediate antiandrogen switching from bicalutamide (BCL) to flutamide (FLT) in patients receiving combined androgen blockade for advanced prostate cancer. From 2002 to 2006, 20 patients who showed PSA failure after first-line hormonal therapy with a luteinizing hormone-release hormone (LH-RH) agonist and BCL were enrolled. All patients were immediately switched from BCL to FLT, administered with an LH-RH agonist, as second-line combined androgen blockade (CAB). We evaluated the PSA response to second-line CAB. Eight patients (40%) were responsive, showing PSA decreases of at least 50%. The median (range) duration of the PSA response was 18.4 (3–26) months. Second-line CAB using FLT was effective in 40% of patients who received first-line CAB using BCL. The lower Gleason scores at the initial prostate biopsy probably reflect the response to second-line CAB. Responders showed significantly better OS and CSS in the determination of any PSA decline and 40% PSA decline. The median OS duration in nonresponders and responders (40% PSA decline) was 1433 days versus 3617 days. It is concluded that an immediate switch from BCL to FLT is effective for some CRPC patients after first-line CAB using BCL.